Factor that influence consumers' willingness to choose microfinance facility at Bank Kerjasama Rakyat Malaysia Berhad (BKRM) / Nor Hazirah Khamis - Khamis, Nor Hazirah (Faculty of Business Management, 2018)
Banking institutions must take the challenges and support the growth of local micro and SMEs, as they are the promoter of equitable development in the economy. However, there are lack of assessment on the microfinance facilities offer by the banking institution. Then this study have been conducted to focus on the microfinance facilities under banking institutions, which is Bank Kerjasama Rakyat Malaysia Berhad (Bank Rakyat). In the study, the researcher uses theory of interpersonal behaviour factor to determine the willingness of the consumers to choose microfinance facility offer by BKRM. Several factor are used for determine consumers' willingness to choose (dependent variable) such as social factors, perceived financial benefit and perceived risk (independent variables). The finding of the study found that consumers' willingness to choose microfinance facility at Bank Rakyat is significantly influenced by perceived financial benefit when receiving the micro- financing. Others factors found to influence the respondents' willingness to choose microfinance at Bank Rakyat is perceived risk associated in it. Thus, it is suggested that Bank Rakyat should provide more attractive benefits and reduce the risk. In particular, give opportunity to new comer of SMEs who have profitable business venture to gain high margin of financing.